Trends : The Shifting Urban Economic Landscape, What Does It Mean for Cities? - Dobbs, Richard; Remes, Jaana (World Bank, Washington, DC, 2014)
Cities are the driving force of economic growth. According to the United Nations, more than half the world's people now live in urban areas - in towns and in cities of all sizes. By 2025, the urban population is expected to have grown by another billion people, a huge majority of them in developing countries. At that point, 2.5 billion people - more than half the world's urban population will likely live in the burgeoning cities of Asia. China is expected to have more than triple, and India double, the number of urbanites in the United States today. Urbanization is not new. For centuries, people have packed up and moved from their rural homes in search of better-paid urban livelihoods. But today's urban shift is unprecedented in scale and speed. It is no hyperbole to say that one is amid the most significant economic transformation the world has ever seen.